Analisis Struktur Modal, Kebijakan Deviden, Keputusan Investasi, dan Inflasi dengan Profitabilitas sebagai Variabel Intervening terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Perkebunan yang Terdaftar Di BEI Tahun 2016 – 2021) - Novita Manda Sari Tanjung; Suyanto Suyanto; Jesica Virdayanti (J-MAS (Jurnal Manajemen dan Sains), 2022)
The aim of the study is to determine whether the factors of capital structure, dividend policy, investment choices, and inflation have a direct or indirect impact on the profitability of plantation companies on the IDX between 2016 and 2021. From 2016 to 2021, this study focuses on 15 plantation companies on the IDX. The eight plantation companies on the IDX are a sample size that meets the specified requirements. Secondary data from BEI and BI are used quantitatively. Panel data regression analysis with Smart PLS program and a significance level of 10% is a data analysis method that has been applied. The results showed that firm value was positively and significantly influenced by capital structure, dividend policy, inflation, and profitability. Investment choices also affect firm value positively but not significantly. In addition, capital structure, investment choices, and inflation have a positive but not significant impact on profitability, while dividend policy has a positive but quite large impact. Profitability can reduce how negatively dividend policy affects firm value. On the other hand, profitability cannot reduce the influence of the relationship between capital structure, investment choice, and inflation on firm value.